Releasing the Feminine Voice: A Cavellian Epistemology for the Philosophy of Religion - Viefhues-Bailey, Ludger H. (Modern theology, 2011)
How can we imagine anew the discipline of philosophy of religion, given the feminist critiques that it privileges thinking driven by the needs of male subject formation? I address this question first by arguing with Cavell that a specific masculine aversion of erotic reciprocity produces a particular skeptical epistemology. Overcoming this phallocentric thinking requires therefore a new eros. Secondly, I will argue that the fluidly gendered subjectivities I detect in Cavell's work on film enable such a new erotic and epistemic orientation. I conclude by outlining the consequences of this orientation for the pursuits of philosophy of religion.